Influence of aerobic fitness on ratings of perceived exertion during graded and extended duration cycling - Green, J. M.; Pritchett, R. C.; Mclester, J. R.; Crews, T. R.; Tucker, D. C. (The Journal of Sports Medicine and Physical Fitness, 2007)
Aim: Ratings of perceived exertion (RPE) have been shown similar across subjects of varying fitness when estimations are made at relative physiological criteria. Because few studies have investigated the influence of fitness during longer duration bouts, the current investigation compared overall exertion (RPE-O), leg exertion (RPE-L) and breathing/chest exertion (RPE-C) between aerobically fit and unfit subjects. Methods: Aerobically fit (61.6±2.5 mL·kg·min-1) (n=7) and unfit (41.8±6.3 mL·kg·min-1) (n=6) males completed a maximal bike test and then cycled for 60 min at ~90% of individualized ventilatory threshold (VT) (VE/VO2 vs VE/VCO2). Heart rate (HR, b·min -1), rectal temperature (Tre, ºC) and RPE estimations were collected during graded testing every 2 min and every 10 min during 60 min bouts. Results: During graded testing, RPE estimations at VT were not significantly different between groups. During 60 min cycling, HR and Tre were not significantly different between groups. Also, there were no significant differences for HR increase (HR 60 min HR 5 min) or Tre increase (Tre 60 min Tre 5 min). Interactions between groups were; RPE-O (P=0.09), RPE-L (P=0.06) and RPE-C (P=0.19). Analyses suggest groups experienced similar relative cardiovascular (HR) and thermal (Tre) strain. Conclusion: Although RPE responses between groups were similar at 10, 20 and 30 min, RPE drift was magnified in aerobically unfit subjects (vs aerobically fit subjects) beyond the 30 min point. Contrary to previous studies suggesting aerobic fitness does not influence RPE, current results show lower aerobic fitness magnifies RPE at individualized relative intensities when cycling extends beyond 30 min.